Collaboration Initiative on Green Construction and Sustainability through Industrialized Buildings Systems (IBS) in the Malaysian Construction Industry - Mohamad Kamar, Kamarul Anuar; Abd. Hamid, Zuhairi; Ghani, Mohd Khairolden; Egbu, Charles; Arif, Mohammed (International Journal of Sustainable Construction Engineering and Technology, 2011)
Malaysian Construction Industry has been urged to use innovative construction technique and to shift from traditional practice of brick and mortar to Industrialized Building System (IBS) construction. IBS is defined as a construction technique in which components are manufactured in a controlled environment (on or off site), transported, positioned and assembled into a structure with minimal additional site works. On the other hand, the issues of sustainability and green construction have been duly highlighted in the Construction Industry Master Plan (2005 – 2015) as being of significant importance for the Malaysian construction industry. The Malaysian government is also committed to addressing sustainability issues and meeting its target and obligations in this regard. This paper highlights several aspects of IBS that has the potential of contributing to green construction and sustainability. IBS promotes sustainability from controlled production environment, minimization of waste generation, extensive usage of energy efficient building material, effective logistics and long term economic stability which can contribute to better investment in environment technologies. The Construction Research Institute of Malaysia (CREAM), University of Salford and other research institutes in Malaysia will conduct a collaboration Research and Development (R&D) initiative on green construction and sustainability trough IBS implementation. From this paper, the authors hope to receive feedbacks, comments and recommendations to improve research aims, objectives, expected deliverables and research methodology.